Prostate cancer targeted multifunctionalized graphene oxide for magnetic resonance imaging and drug delivery. (October 2016) - Guo, Linlin; Shi, Haili; Wu, Huixia; Zhang, Yixue; Wang, Xue; Wu, Dongmei; An, Lu; Yang, Shiping
Abstract: Dendrimers capped with amino groups (DEN) are grafted to graphene oxide (GO) nanosheets for subsequent functionalization of GO with gadolinium diethylene triamine pentaacetate (Gd-DTPA) and prostate stem cell antigen (PSCA) monoclonal antibody (mAb). The as-prepared GO-DEN(Gd-DTPA)-mAb exhibits very low cytotoxicity, negligible hemolytic activity, and no perceptible toxic effects in mice. GO-DEN(Gd-DTPA)-mAb can specifically target PSCA over-expressed cancer cells to give a significant T1 -weighted contrast enhancement effect. The in vivo magnetic resonance imaging results indicate that GO-DEN(Gd-DTPA)-mAb can be used as a targeted contrast agent for prostate tumor imaging. GO-DEN(Gd-DTPA)-mAb can be efficiently loaded with doxorubicin hydrochloride (DOX), and the resulting GO-DEN(Gd-DTPA)-mAb/DOX exhibits enhanced cytotoxicity to PC-3 cells due to good targeting performance. By following the PC-3 tumor growth in mouse model after intravenous administration of GO-DEN(Gd-DTPA)-mAb/DOX, it is demonstrated that GO-DEN(Gd-DTPA)-mAb can targetedly deliver anticancer drugs to malignant prostate tumors and inhibit tumor growth.